The impact of adopting AI tools on enhancing customer experience: Case study of mobilis enterprise-Algeria - Khadich, Ghada; Boulkara, Amina (The International tax journal, 2026)
Customers are the foundation of every business, and enhancing their experience has become a strategic priority in today’s competitive market. The adoption of Artificial Intelligence (AI) tools plays a crucial role in achieving this goal by enabling organizations to better understand, predict, and respond to customer needs. AI tools, such as chatbots, recommendation systems, and predictive analytics, help businesses personalize interactions, improve service efficiency, and strengthen customer relationships. This study explores the impact of adopting AI tools on enhancing customer experience, focusing on how these technologies bridge the gap between businesses and clients through data-driven insights and intelligent automation. An exploratory-hypothesis-deductive approach is employed to conceptualize a model that explains the relationship between AI adoption and customer experience improvement. The study offers valuable implications for practitioners in developing AI-driven strategies, for managers in integrating AI into customer service frameworks, for researchers in expanding the marketing technology literature, and for society by promoting more satisfying and engaging customer experiences.